Pengaruh Kemandirian, Pengalaman Kerja, dan Akuntabilitas terhadap Tindakan dalam Meningkatkan Kualitas Audit - Agusti, Rahmadina; Hartono, Budi; Lubis, Maksum Syahri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Audit quality is one of the important prerequisites in conducting an audit. This is to evaluate audit quality and several factors that affect audit quality at various levels of audit engagements. By definition, audit quality is achieved when the auditor can identify material items by applying Generally Accepted Auditing Standards and Principles that help ensure the accuracy of the auditor's actions and reports. This study aims to analyze whether there is an effect of independence, work experience, and accountability on actions to improve audit quality, either partially or simultaneously. The method used is descriptive quantitative, using a questionnaire and a Likert scale. The total population is 163 employees. The sample measurement technique is the slovin formula, resulting in a total sample of 115 employees. The data analysis technique used multiple linear regression, and hypothesis testing using T test and F test. The results of the study found that there was no influence between independence on actions to improve audit quality, but there was a significant effect between work experience and accountability on actions in improving audit quality. partially or simultaneously.